The Gut Microbiota: A Novel Player in Autoimmune Hepatitis - Cheng, Zilu; Yang, Ling; Chu, Huikuan (Frontiers in Cellular and Infection Microbiology, 2022)
Autoimmune hepatitis (AIH) is a chronic immune-mediated liver disease distributed globally in all ethnicities with increasing prevalence. If left untreated, the disease will lead to cirrhosis, liver failure, or death. The intestinal microbiota is a complex ecosystem located in the human intestine, which extensively affects the human physiological and pathological processes. With more and more in-depth understandings of intestinal microbiota, a substantial body of studies have verified that the intestinal microbiota plays a crucial role in a variety of digestive system diseases, including alcohol-associated liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD). However, only a few studies have paid attention to evaluate the relationship between AIH and the intestinal microbiota. While AIH pathogenesis is not fully elucidated yet, some studies have indicated that intestinal microbiota putatively made significant contributions to the occurrence and the development of AIH by triggering several specific signaling pathways, altering the metabolism of intestinal microbiota, as well as modulating the immune response in the intestine and liver. By collecting the latest related literatures, this review summarized the increasing trend of the aerobic bacteria abundance in both AIH patients and AIH mice models. Moreover, the combination of specific bacteria species was found distinct to AIH patients, which could be a promising tool for diagnosing AIH. In addition, there were alterations of luminal metabolites and immune responses, including decreased short-chain fatty acids (SCFAs), increased pathogen associated molecular patterns (PAMPs), imbalanced regulatory T (Treg)/Th17 cells, follicular regulatory T (TFR)/follicular helper T (TFH) cells, and activated natural killer T (NKT) cells. These alterations participate in the onset and the progression of AIH via multiple mechanisms. Therefore, some therapeutic methods based on restoration of intestinal microbiota composition, including probiotics and fecal microbiota transplantation (FMT), as well as targeted intestinal microbiota-associated signaling pathways, confer novel insights into the treatment for AIH patients.